ChemInform Abstract: Dialkylation of Diethyl Ethoxycarbonylmethylphosphonate under Microwave and Solventless Conditions. Issue 32 (24th July 2014) - Gruen, Alajos; Blastik, Zsofia; Drahos, Laszlo; Keglevich, Gyoergy
Abstract A multistep microwave‐assisted, solvent‐ and catalyst‐free method for the 2, 2‐Dialkylation of the title methylphosphonate (I) is developed.